Phase II study of vincristine, actinomycin-D, cyclophosphamide and irinotecan for patients with newly diagnosed low-risk subset B rhabdomyosarcoma: A study protocol - Miyachi, Mitsuru; Tsuchiya, Kunihiko; Hosono, Ako; Ogawa, Atsushi; Koh, Katsuyoshi; Kikuta, Atsushi; Hara, Junichi; Teramukai, Satoshi; Hosoi, Hajime (Medicine (Baltimore), 2019)
Approximately 80% to 90% of patients with low-risk rhabdomyosarcoma can be cured. However, cured patients often face long-term complications associated with the treatment. An important factor in the treatment plan is the dose of cyclophosphamide administered because the dose can have both acute and long-term side effects. It is therefore essential to investigate whether the dose can be reduced without a negative effect on treatment outcome. The ARST0331 trial revealed that drastically reducing the cyclophosphamide dose to 4.8 g/m negatively affected treatment outcomes. The current study aims to determine whether reducing the cyclophosphamide dose to 10.8 g/m while introducing a new drug, irinotecan, can prevent the negative effect on treatment outcome. We also aim to investigate whether the reduced cyclophosphamide dose results in a decrease in infertility, one of the long-term complications of this treatment. The subjects are patients with stage 1 group III rhabdomyosarcoma (excluding those with orbital group III N0 and NX) or patients with stage 3 group I and II low-risk subset B embryonal rhabdomyosarcoma who will alternately undergo VAC 1.2 treatment (vincristine, actinomycin D, cyclophosphamide 1.2 g/m) and VI treatment (vincristine, irinotecan). The effectiveness and safety of this treatment regimen will be assessed. Data will be presented at international conferences and will be published in peer-reviewed journals. This study is significant because it aims to establish that the use of irinotecan in patients with low-risk subset B embryonal rhabdomyosarcoma (aged 30 or younger) allows the dose of cyclophosphamide to be reduced and is associated with few short-term adverse effects and long-term complications. The open-label and single-arm design of this study may be a limitation. The trial registration number is jRCTs051180200 (Japan Registry of Clinical Trials). The study protocol was approved by the institutional review board at each of the participating centers and the data will be presented at international conferences and published in peer-reviewed journals.